THE EFFECT OF SLEEP QUALITY ON GRADE POINT AVERAGE AND CLINICAL EXAMINATION SCORES IN NORTHERN BORDER UNIVERSITY MEDICAL STUDENTS - ABDELRAHMAN MOHAMED AHMED ABUKANNA; ALMUJTABA ALSHANGITY; HAFIZ OSMAN IBN IDRIS ALMISBAH; MOHAMMED OBAID ALENAZI; ZAKARIYA M S MOHAMMED; OMAIMA A HAMID (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Sleep disturbances are more common in medical students than in non-medical students and the general population. This study aimed to evaluate the sleep quality of medical students at Northern Border University in relation to their clinical examination scores. Methods: We used a cross-sectional design that involved medical students in their clinical years at Northern Border University. A pre-designed questionnaire was administered online. The relationships between Grade Point Average (GPA) and Pittsburgh Sleep Quality Index (PSQI) and GPA and Epworth Sleepiness Scale (ESS) were evaluated using correlation coefficients. IBM SPSS (version 26, SPSS Inc., Chicago, IL, USA) was used. Results: A total of 247 students participated in the study. The leading cause of disturbed sleep was the inability to sleep within 30 min. Suffering from mild to very severe difficulty in falling asleep was found in (58.7%), followed by “difficulty staying asleep” in (41.7%) and “problems waking up too early” in (38.9%). Regarding the impact of sleep quality on clinical test scores, (59.9%) indicated that it has a negative effect. There was a weak negative correlation between students’ GPA and ESS, as well as GPA and PSQI. Conclusion: A significant percentage of the study group had bad sleep quality. The most important reasons for the bad sleep quality were difficulty staying asleep and waking up early. Most of the study group came to the clinical examinations without sleeping the night before, negatively affecting their examination scores. The study found a significant negative correlation between sleep quality and academic performance.